2015
DOI: 10.1007/s10549-015-3374-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with genetic counseling and BRCA testing in a population-based sample of young Black women with breast cancer

Abstract: Purpose Concerns about the potential for genomic advances to increase health disparities have been raised. Thus it is important to assess referral and uptake of genetic counseling (GC) and testing in minority populations at high risk for hereditary breast and ovarian cancer (HBOC). Methods Black women diagnosed with invasive breast cancer ≤ age 50 in 2009-2012 were recruited through the Florida State Cancer Registry 6-18 months following diagnosis and completed a baseline questionnaire. Summary statistics, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 35 publications
4
80
3
Order By: Relevance
“…The relatively small sample size and homogenous study population (well educated, non-Hispanic white, married) are limitations and underscore the need to replicate our findings with diverse populations. Interest in gene-panel testing may be determined by other factors such as cost, concern about genetic discrimination, and the perceived benefit of the genetic information assessed, including the likelihood of clear risk management strategies (BradburyPatrick-Miller & Domchek, 2015; Cragun et al, 2015; Easton et al, 2015; Powers et al, 2014). Finally, gene-panel testing is a complicated and rapidly evolving field.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small sample size and homogenous study population (well educated, non-Hispanic white, married) are limitations and underscore the need to replicate our findings with diverse populations. Interest in gene-panel testing may be determined by other factors such as cost, concern about genetic discrimination, and the perceived benefit of the genetic information assessed, including the likelihood of clear risk management strategies (BradburyPatrick-Miller & Domchek, 2015; Cragun et al, 2015; Easton et al, 2015; Powers et al, 2014). Finally, gene-panel testing is a complicated and rapidly evolving field.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be suggestive that factors in the participants' lives other than emotions have been demonstrated as impactful on decisions and attitudes towards genetic testing [18,24,25]. Ethnic populations with inherently stronger opinions about genetic testing or low-income parents who believe the costs of testing to be out of their possibilities of care may use these traits as a prevailing basis for their opinion [26].…”
Section: Limitationsmentioning
confidence: 99%
“…(911) Studies have suggested that physician recommendation and referral patterns may influence patients’ access to standard of care cancer genetics services. (1215)…”
Section: Introductionmentioning
confidence: 99%